(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study assessed available ICT resources for teaching business education courses in tertiary institutions in South South Nigeria. One research question was raised and answered while two null hypotheses were tested at 0.05 level of significance. The descriptive survey design was adopted for the study. The population comprised all 240 business educators in the colleges of education and universities in this area. The entire population was used. A structured questionnaire was used as instrument for data collection. Kunder Richardson statistics was used to establish the reliability; a reliability coefficient of 0.73 was obtained. Data collected were analyzed using percentage, mean and standard deviation to answer the research question and the null hypotheses were tested at 0.05 level of significance using t-test statistics. The findings showed there are no ICT resources for teaching business education courses and that college of education have more ICT have more ICT resources than the universities. Conclusions were drawn and relevant recommendations were made among others that government and relevant stake- holders should provide adequate and relevant ICT resources for the teaching of business education courses in tertiary institutions.